Hadith #996 - Sahih Muslim - Rabi'a bin 'Uthman bin Rabi'a ربيعة بن عثمان بن ربيعة (Sahih Muslim)
I was with Allah’s Messenger (ﷺ) one night. and I brought him water and what he required. He said to me: Ask (anything you like). I said: I ask your company in Paradise. He (the Holy Prophet) said: Or anything else besides it. I said: That is all (what I require). He said: Then help me to achieve this for you by devoting yourself often to prostration.
Grade: Sahih

Hadith #2366 - Sahih Muslim - Rabi'a bin 'Uthman bin Rabi'a ربيعة بن عثمان بن ربيعة (Sahih Muslim)
Go to the Messenger of Allah (ﷺ), and the rest of the hadith is the same (but with this addition):” ‘Ali spread his cloak and then lay down on it and said: I am the father of Hasan, and I am the chief. By Allah, I would not move from my place till your sons come back to you with the reply to that for which you sent them to the Messenger of Allah (ﷺ). And he then also said: Verily these sadaqat are the impurities of people, and they are not permissible for Muhammad (may peaace be upon him
Grade: Sahih

Hadith #4370 - Sahih Muslim - Rabi'a bin 'Uthman bin Rabi'a ربيعة بن عثمان بن ربيعة (Sahih Muslim)
” There came a person to Allah’s Messenger (ﷺ) while I was with him, and he asked him about picking up of a stray article, and he said: When none comes to demand it, then spend that.”
Grade: Sahih